Perceived Effects of Quality of Pre-Primary Education Services on Parents ' Satisfaction in Dar es Salaam, Tanzania - Mabagala, Daphina Libent (Papers in Education and Development, 2022)
This study investigated the effects of perceived quality of service dimensions on parents ' satisfaction with pre-primary education in Dar es Salaam region. A descriptive survey research design guided the study and selfadministered questionnaire was used to collect data from a sample of 772 parents with children in pre-primary classrooms. Descriptive and inferential statistics were employed to analyse data. Results revealed that four dimensions in perception of quality, namely classroom characteristics, teacher behaviour, parents ' involvement and physical environment had a significant and positive effect on overall parents ' satisfaction. These results indicate that quality of pre-primary education service is indeed a significant predictor of parents ' satisfaction. Thus, improving quality of pre €“ primary education service results in higher satisfaction levels of parents. Keywords: parents ' perception, parents ' satisfaction, quality of pre-primary education